Psychological determinants of resilience: theoretical analysis of personal and coping approaches - Rudenko, Liliya; Druz, Oleh; Rodchenko, Larisa; Semenets-Orlova, Inna; Velgan, Oleksandr (My University, 2023)
In today's environment, the issue of personal resilience is becoming increasingly important. The issue of a person's ability to overcome difficult life situations, adapt to stressful conditions and return to balance is relevant. The article presents a theoretical analysis of the psychological determinants of resilience: personal traits and coping behaviour. The content of the concept of "resilience" by scientists is presented. Four main trajectories of resilience development are allocated. It is stated that it is important to consider resilience as a stable and at the same time dynamic phenomenon associated with mental wellbeing, health and features of coping that may be its consequences. It is noted that training in more effective coping strategies can increase resistance at the biological level. Resilience is the process and outcome of successfully adapting to difficult or challenging life experiences, especially through mental, emotional, and behavioral flexibility and adjustment to external and internal demands. The impact on the functional activity of the brain by forming adaptive cognitive, emotional and behavioural patterns of stress response will strengthen the weak links of the human stress system. This suggests that resilience should be considered both as a trait that is relatively stable, caused by internal and external factors, and as a dynamic process, as resilience is formed, develops and has its own dynamics throughout life. It has been determined that some personality traits (serving as a foundation) and coping strategies (being mechanisms) contribute to the development of resilience. У сучасних умовах питання особистісної стійкості набуває дедалі більшої актуальності. Актуальним є питання здатності людини долати складні життєві ситуації, адаптуватися до стресових умов та повертатися до рівноваги. У статті представлено теоретичний аналіз психологічних детермінант стійкості: особистісних рис та поведінки подолання. Представлено зміст поняття «стійкість» вченими. Виділено чотири основні траєкторії розвитку стійкості. Зазначається, що важливо розглядати стійкість як стабільне та водночас динамічне явище, пов'язане з психічним благополуччям, здоров'ям та особливостями подолання, які можуть бути його наслідками. Зазначається, що навчання більш ефективним стратегіям подолання може підвищити стійкість на біологічному рівні. Стійкість – це процес і результат успішної адаптації до складного або викликного життєвого досвіду, особливо через психічну, емоційну та поведінкову гнучкість та адаптацію до зовнішніх і внутрішніх вимог. Вплив на функціональну активність мозку шляхом формування адаптивних когнітивних, емоційних та поведінкових моделей реагування на стрес посилить слабкі ланки стресової системи людини. Це говорить про те, що стійкість слід розглядати як рису, що є відносно стабільною, зумовлену внутрішніми та зовнішніми факторами, так і як динамічний процес, оскільки стійкість формується, розвивається та має свою власну динаміку протягом життя. Визначено, що деякі риси особистості (які слугують основою) та стратегії подолання (які є механізмами) сприяють розвитку стійкості.
Keywords: resilience; стійкість; копінг-стратегії; coping strategies; wartime; воєнний час